The Reciprocal Teaching and Reading Interest Impact on Students’ Reading Comprehension - Wahyudi , Ridwan; Rozimela, Yenni (Universitas Lancang Kuning, 2024)
This study uniquely explores the combined impact of reciprocal teaching and reading interest on reading comprehension, an intersection rarely examined. This study investigates the effectiveness of the reciprocal teaching method and students’ reading interest on reading comprehension in an Integrated Islamic School. A quasi-experimental design was employed, involving 56 students divided into an experimental group (n = 29) and a control group (n = 27). The experimental group received reciprocal teaching, while the control group followed conventional methods. Reading comprehension was assessed using a standardized reading test, and reading interest was measured through a questionnaire. The data were analyzed using t-tests and correlation analysis. The findings revealed that the experimental group performed significantly better than the control group, achieving an average reading comprehension score of 91.92, while the control group scored 77.99. This difference was statistically significant, demonstrating a strong impact of reciprocal teaching on students' comprehension abilities (p < 0.001). Moreover, students with high reading interest in the experimental group demonstrated superior comprehension, with a mean score of 94.31, compared to 91.41 in the control group. The results demonstrate the effectiveness of reciprocal teaching in boosting reading comprehension, especially for students with a strong interest in reading. The study suggests that reciprocal teaching is a valuable method for enhancing reading engagement and comprehension, offering useful insights for educators and policymakers focused on improving literacy outcomes.